Jon Elster's Securities against Misrule: Juries, Assemblies, Elections: A Review Essay - Austen-Smith, David (Journal of Economic Literature, 2015)
The standard economic approach to designing institutions for collective decision making recognizes individuals' strategically rational motivations for misrepresentation and asks how best, given an objective function, to design a set of incentives and constraints to internalize or negate such motivations. Securities Against Misrule offers, in the author's phrase, an “essay in persuasion” to the effect that such an approach is fundamentally misguided. Instead, Elster argues for a behavioral approach centered on designing institutions for good decision making, rather than good outcomes, by individuals whose actions are chronically subject to emotional, self-interested, and prejudicial distortions. (JEL D02, D71, D72, D82)